2002
DOI: 10.1029/2002gl015609
|View full text |Cite
|
Sign up to set email alerts
|

Lidar backscatter to extinction, mass and area conversions for stratospheric aerosols based on midlatitude balloonborne size distribution measurements

Abstract: Size distributions of the stratospheric sulfuric acid aerosol derived from balloonborne particle counter measurements from Laramie, Wyoming, are used to calculate ratios of particle extinction, mass, and surface area to particle backscatter, and the wavelength dependences of particle backscatter and extinction. These ratios may then be used to infer particle extinction, mass, and area from midlatitude lidar data in the spectral range 355 nm to 1064 nm for the time period 1991 to 1999. The conversions are defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 13 publications
(18 reference statements)
6
83
1
Order By: Relevance
“…The integrated backscatter from these profiles (calculated using the CIRA standard atmosphere) was in the range 2-7×10 −5 sr −1 . This is in agreement with Jäger et al (2001), and using a ratio of extinction to backscatter appropriate to post-Pinatubo aerosol of 50 sr (Jäger andDeshler, 2002, 2003) it corresponds to an optical depth of 1-3.5×10 −3 . …”
Section: Measurements Of Background Aerosolsupporting
confidence: 77%
See 1 more Smart Citation
“…The integrated backscatter from these profiles (calculated using the CIRA standard atmosphere) was in the range 2-7×10 −5 sr −1 . This is in agreement with Jäger et al (2001), and using a ratio of extinction to backscatter appropriate to post-Pinatubo aerosol of 50 sr (Jäger andDeshler, 2002, 2003) it corresponds to an optical depth of 1-3.5×10 −3 . …”
Section: Measurements Of Background Aerosolsupporting
confidence: 77%
“…These values are consistent with a Type 1a PSC (Toon et al, 1990), where a small number of relatively large particles give high depolarisation but little backscatter. This time, the minimum temperatures between 100 and 30 mb were <194 K, and maps of the 50 mb temperature field from ECMWF (obtained from the NADIR data base, NILU, Norway) showed an extension of the polar vortex swinging east over the UK between 9 and 10 January; indeed, the ozonesonde launched on the 10 January resulted from an alert issued by the Match project (Rex et al, 2002). Observations on the following night (11/12 January) showed clear PSCs at the beginning of the night but not at the end, consistent with the retreat of the vortex northward during the 11 January.…”
Section: Observations Of Polar Stratospheric Cloudsmentioning
confidence: 99%
“…We derived backscattering ratio profiles with an inversion method (Fernald, 1984). The lidar ratio S (particle extinction to backscatter ratio) is dependent on the stratospheric aerosol size distribution and refractive index, and equalled 20-60 sr at 532 nm during 1979-1999(Jäger and Deshler, 2002 We obtained IBCs by summing up BAs from the first tropopause height to an altitude of 33 km. When cirrus clouds appeared above the tropopause, we set the lower limit of the integration to just above the altitude of the cirrus clouds.…”
Section: Lidar Instruments and Data Analysismentioning
confidence: 99%
“…This value is commonly used for volcanically quiescent conditions and periods of moderate eruptions (Sakai et al, 2016). The lidar ratio depends on the particle size distribution and the type of aerosol (Jäger and Deshler, 2002;Young and Vaughan, 2009). Error in the lidar ratio could significantly influence the uncertainty in aerosol extinction and optical depth (Sakai et al, 2016;Khaykin et al, 2017).…”
mentioning
confidence: 99%
“…Based on the control of the stratospheric aerosol burden over the last 25 years, Thomason et al (2007) showed that volcanic effects dominate over natural and anthropogenic sources. Previous studies on stratospheric aerosols have significantly characterized its properties and variability during "background" (i.e., free of volcanic aerosols) and volcanic conditions (e.g., Stenchikov et al, 1998;Jäger and Deshler, 2002;Bauman et al, 2003;Hermann et al;Hofmann et al;.…”
mentioning
confidence: 99%